Pengaruh Dukungan Otonomi dan Efikasi Diri terhadap Kepuasan melalui Komitmen Organisasi - Trisna Kiki Wijayanti; Dwiarko Nugrohoseno (BISMA (Bisnis dan Manajemen), 2018)
Autonomy support that given to employees is supported by the self-efficacy of employees, it will increase the employee job satisfaction and organizational commitment. With a sample of 97 employees at PT. Boma Bisma Indra (Persero) Surabaya, using SEM Smart PLS 2.0 analysis techniques. The result that is a significant effect of autonomy support on organizational commitment and job satisfaction, a significant effect of self efficacy on organizational commitment and job satisfaction, a significant effect of organizational commitment on job satisfaction, no significant effect of autonomy support on job satisfaction mediated by organizational commitment and no significant effect of self efficacy on job satisfaction mediated by organizational commitment.Autonomy support that given to employees is supported by the self-efficacy of employees, it will increase the employee job satisfaction and organizational commitment. With a sample of 97 employees at PT. Boma Bisma Indra (Persero) Surabaya, using SEM Smart PLS 2.0 analysis techniques. The result that is a significant effect of autonomy support on organizational commitment and job satisfaction, a significant effect of self efficacy on organizational commitment and job satisfaction, a significant effect of organizational commitment on job satisfaction, no significant effect of autonomy support on job satisfaction mediated by organizational commitment and no significant effect of self efficacy on job satisfaction mediated by organizational commitment.